A registered re-examination of the effects of leftward prism adaptation on landmark judgements in healthy people. (January 2023) - McIntosh, Robert D.; Ten Brink, Antonia F.; Mitchell, Alexandra G.; Jones, Hannah; Peng, Nan; Thye, Melissa; Bultitude, Janet H.
Abstract: It has long been known that active adaptation to a shift of the visual field, caused by laterally-displacing prisms, induces short-term sensorimotor aftereffects. More recent evidence suggests that prism adaptation may also stimulate higher-level changes in spatial cognition, which can modify the spatial biases of healthy people. The first reported, and most replicated, higher-level aftereffect is a rightward shift in the point of subjective equality (PSE) for a perceptual bisection task (the landmark task), following adaptation to leftward prisms. A recent meta-analysis suggests that this visuospatial aftereffect should be robustly induced by an extended period of adaptation to strong leftward prisms (15°, ∼26.8 prism dioptres). However, we have been unable to replicate this effect, suggesting that the effect size estimated from prior literature might be over-optimistic. This Registered Report compared visuospatial aftereffects on the landmark task for a 15° leftward prism adaptation group ( n  = 102) against a sham-adaptation control group ( n  = 102). The effect size for the comparison was Cohen's d  = .27, 95% CI [-.01, .55], which did not pass the criterion set for significance. A Bayesian analysis indicated that the data were more than 4.1 times as likely under the null than under an informed experimental hypothesis. Exploratory analyses showed no evidence for a rightward shift of landmark judgements in the prism group considered alone, and no relationship between sensorimotor and visuospatial aftereffects. We further found no support for previous suggestions that visuospatial aftereffects are modulated by a person's baseline bias (leftward or rightward) for the landmark task. Null findings are also presented for a preliminary group of 62 participants adapted to 15° leftward prisms, and an additional group of 29 participants adapted to 10° leftward prisms. We do not rule out the possibility that leftward prisms might induce higher-level visuospatial aftereffects in healthy people, but we should be more sceptical about this claim.